Evaluating bone biopsy quality by technique in an animal model - Corey K Ho, MD; David Gimarc, MD; Hsieng-Feng Carroll, PhD; Michael Clay, MD; Jeffrey Schowinsky, MD; MK Jesse, MD; Amanda M Crawford, MD; Carrie B Marshall, MD (Research in Diagnostic and Interventional Imaging, 2022)
Rationale and Objectives: Powered bone biopsy technique is popular due to its ease of use. However, there is conflicting evidence regarding the diagnostic quality of the samples. The purpose of this study is to evaluate the diagnostic adequacy of different bone biopsy devices and techniques as it relates to the frequency of sample artifacts. Materials and Methods: Bone biopsy was performed on same-day processed lamb femora using the following techniques: manual, pulsed powered and full powered. Ten samples were collected using each method by a single musculoskeletal-trained radiologist and were reviewed by 3 blinded pathologists. Samples were compared across multiple categories: length, bone dust, thermal/crush artifact, cellular morphology, fragmentation, and diagnostic acceptability. Bayesian Multilevel Nonlinear Regression models were performed assessing the association between the techniques across the categories. Results: Statistical analysis revealed that the manual technique outperformed any powered technique across all categories: decreased thermal/crush artifact (P = 0.014), decreased bone dust (p<0.001), better cellular morphology (P = 0.005), less fragmentation (P < 0.0001) and better diagnostic acceptability (P < 0.0001). Conclusion: Manually obtained bone biopsy samples generally produce a more diagnostic sample as compared to powered techniques in an animal model. Given these results, manual bone biopsy methods should be encouraged after consideration for lesion composition, difficulty of access and the patient's overall condition.